The Effectiveness of using the Hijaiyah Game within the Natural Method to enhance writing skills - Hilira, Anggini Putri; Kasmiati, Kasmiati; Halomoan, Halomoan; Syaf, Moh. Najib (Universitas Negeri Padang, 2024)
It was experiment research aiming at finding out the effectiveness of Natural method with Hijaiyah game in increasing student writing ability at the fourth grade of Islamic Integrated Elementary School of An-Najiyah. The formulation of the problem in this research was